ON THE PROBLEM OF DETERMINING THE AMOUNT OF AIR SURROUNDING THE SURFACES OF DIFFERENT TYPES OF DISKS IN A DISK-SHOE BRAKE - Вольченко, Дмитро Олександрович; Журавльов, Дмитро Юрійович; Кашуба, Микола Васильович; Стадник, Олег Богданович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The paper deals with the problem of determining the amount of air surrounding mat and polished surfaces of different types of disks in a disk-block brake on the basis of the energy balance of high-speed air currents considering the convective and radiative heat exchange. However, these methods do not always take into account the heat emission from the surfaces of different types of disks into the environment having a significant impact on the finite friction temperature, especially when driving a vehicle. Therefore, the suggested mathematical description of the energy balance of the high-speed air currents surrounding the polished and mat surfaces of the disks taking into account the convective and radiative cooling on the basis of its quantity will allow to evaluate the reduction of the energy-loading of friction pairs of the brake.